2009
DOI: 10.3390/rs1030393
|View full text |Cite
|
Sign up to set email alerts
|

Potential Species Distribution of Balsam Fir Based on the Integration of Biophysical Variables Derived with Remote Sensing and Process-Based Methods

Abstract: Abstract:In this paper we present a framework for modelling potential species distribution (PSD) of balsam fir [bF; Abies balsamea (L.) Mill.] as a function of landscape-level descriptions of: (i) growing degree days (GDD: a temperature related index), (ii) landsurface wetness, (iii) incident photosynthetically active radiation (PAR), and (iv) tree habitat suitability. GDD and land-surface wetness are derived primarily from remote sensing data acquired with the Moderate Resolution Imaging Spectroradiometer (MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…The area covers 24,240 km 2 , its boundaries being: north latitude: 46:45:00N, south latitude: 45:36:50N, west longitude: 10:06:33E, and east longitude: 12:46:30E. It is divided by several dominant wide river valleys, for example the territory of the Autonomous Provinces of Trento and Bolzano is bisected from north to south by the Adige river valley, following the south-eastern drainage pattern in this area.…”
Section: Study Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…The area covers 24,240 km 2 , its boundaries being: north latitude: 46:45:00N, south latitude: 45:36:50N, west longitude: 10:06:33E, and east longitude: 12:46:30E. It is divided by several dominant wide river valleys, for example the territory of the Autonomous Provinces of Trento and Bolzano is bisected from north to south by the Adige river valley, following the south-eastern drainage pattern in this area.…”
Section: Study Regionmentioning
confidence: 99%
“…The application of traditional geospatial interpolation methods in complex terrain remains challenging [1] and difficult to optimize. Remote sensing is an alternative data source [2] since remotely sensed imagery is to air temperatures, which are measured at 2 m above ground, it can be assumed that the general temperature profile/patterns are very similar [21].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there is an increasing trend in using remote sensing information based, e.g., on various spectral indices recorded from airborne or space-borne sensors as predictor variables in species distribution modeling [22][23][24][25][26]. A few studies have shown that niche models developed by incorporating remotely-sensed predictors are more robust; in particular, these data can improve the prediction accuracy and tend to refine mapped distribution of species and habitats, compared with climatic/topographical variables-only models [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…임목생장에 영향을 미치는 온도의 효과를 생장도일 의 포물선 함수에 의해 지수화한 것이 온도효과지수이 다 (Botkin et al, 1972;Lim, 1998;Hassan and Bourque, 2009 , 수문지표와 온열지표 (Choi, 2010), 그리고 기온감율을 적용한 공간보간기법 (Lee et al, 2011) (Sykes and Prentice, 1996;Bourque and Hassan, 2008;Hassan and Bourque, 2009;Bourque et al, 2010). (Lim, 1998;Choi et al, 2010;Lee et al, 2011;National Institute of Forest Science, 2015).…”
Section: 서 론unclassified